A natural sound loudness estimation method as a perspective tool for hearing aid fitting in patients with dead cochlear regions - Dorota HOJAN–JEZIERSKA; Ewa SKRODZKA; Edward HOJAN (Archives of Acoustics, 2014)
Hearing aids fitted with the use of classical methods (POGO, NAL, Berger ect.) often do not bring the expected benefit to hearing impaired people with "dead regions", (DRs). For such patients we propose an alternative method of hearing aids fitting, based on perception of natural sounds – The Natural Sounds Loudness Estimation (NSLE) method. Our aim was to check whether patients with such a complicated hearing loss were able to follow loudness changes in the sound material. Four persons (seven ears) with diagnosed DRs were examined. Only one of them was not able to perform the loudness estimation test with satisfactory precision (calculated as a correlation coefficient between sound pressure changes on an original sound track and subjectively perceived changes in loudness). Next, the parameters necessary to proper hearing aid fitting were calculated using the NSLE. Estimated insertion gains (IGs) were generally lower than those predicted by three classical methods used for comparison. Our conclusion is that the NSLE method may be a good option for hearing aids fitting in the case of people with DRs.